2005
DOI: 10.1021/ma047415f
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Regioregular Poly(3-hexylthiophene) Film Morphology and Field-Effect Mobility on Molecular Weight

Abstract: Morphological characterization has been used to explain the previously observed strong correlation between charge carrier mobility measured with thin-film transistors and the number-average molecular weight (MW) of the conjugated polymer regioregular poly(3-hexylthiophene). Atomic force microscopy and X-ray diffraction show that the low-mobility, low-MW films have a highly ordered structure composed of nanorods and the high-mobility, high-MW films have a less ordered, isotropic nodule structure. Modifying the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

75
1,026
4
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,031 publications
(1,107 citation statements)
references
References 36 publications
75
1,026
4
2
Order By: Relevance
“…Here the chain lengths are calculated from the number average molecular weight. Unlike the relatively low MW P3HT forming rigid nanorods composed of extended chain lamellae with a width approximate to single molecular length, 14 our result indicates that polymer chains above certain MW range tend to chain fold several times inside a nanoribbon. Some well-studied polymers such as polyethylene also show relatively little MW dependence of the crystal thickness under certain processing conditions.…”
Section: Structural Characterizationmentioning
confidence: 63%
See 2 more Smart Citations
“…Here the chain lengths are calculated from the number average molecular weight. Unlike the relatively low MW P3HT forming rigid nanorods composed of extended chain lamellae with a width approximate to single molecular length, 14 our result indicates that polymer chains above certain MW range tend to chain fold several times inside a nanoribbon. Some well-studied polymers such as polyethylene also show relatively little MW dependence of the crystal thickness under certain processing conditions.…”
Section: Structural Characterizationmentioning
confidence: 63%
“…[9][10][11] The mobility depends critically on manifold other factors such as molecular weight, interaction between polymer and solvent, and deposition conditions. 12 Recent research by McGehee et al 13,14 and Neher et al, 15 focusing on the effects of molecular weight ͑MW͒, has shown that MW is another dominant factor to affect mobilities by several orders of magnitude in a regime with mobilities less than 10 −2 cm 2 / V s. They found that the mobility increases with MW in spite of reduced crystallinity at higher MW, indicating that charge transport depends on factors other than the degree of crystallinity. Two possible explanations were proposed respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 In transistor studies of P3HT films over a range of MWs, it has been shown that higher MW P3HT has better quality crystallites which are more co-aligned and connected, possibly by individual polymer chains spanning between crystallites 5 leading to high field effect transistor (FET) mobility. Low MW polymer exhibits reduced transistor performance, which has been explained either by grain boundary trapping effects at lower MW, 4 or enhanced out-of-plane backbone twisting, 6 which results in a reduction in backbone planarity and a resulting decrease in effective conjugation length and the efficiency of charge hopping. Solution studies upon higher MW P3HT have also shown that physical entanglements can initiate polymer aggregation in some solvents, which then leads to gellation.…”
Section: Factors Influencing Microstructure Of Conjugated Polymer Filmsmentioning
confidence: 99%
“…[1][2][3] This has been reported in significant detail for many organic electronic devices, in particular organic solar cells and organic transistors, 4 where it has been demonstrated that the behaviour of the polymer depends on its molecular weight, which can be difficult to control and can lead to large differences in device performance. 5 Furthermore, the chain length and its size distribution are also key factors that determine the packing of the polymer chains and their orientation towards the electrodes. 6 Indeed, the distance between the aromatic groups of adjacent chains also varies with the polymeric Mw resulting in different charge mobilities.…”
Section: Introductionmentioning
confidence: 99%